2014
DOI: 10.3109/21681805.2014.938694
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring male cancer patients’ experiences with percutaneous nephrostomy

Abstract: The study describes how nephrostomy is a burdensome intervention accompanied by a plethora of complex physical and psychosocial issues. Having a nephrostomy on a palliative indication has extensive implications for the patients, which should not be neglected or underestimated. Individual assessment of each patient, together with excellent communication regarding the procedure and outcome, is essential. Most patients had frequent contact with the healthcare system and additional support could be offered by a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 12 publications
1
19
0
3
Order By: Relevance
“…Our results are in line with previous studies which demonstrated that neither ADT nor chemotherapy can achieve adequate palliation for the management of locally progressing and symptomatic prostate cancer [23][24][25]. Leibovici et al [24] treated 38 patients with locally advanced primary or recurrent disease by cystoprostatectomy, which led to significant and permanent reduction of symptoms in 30 patients (88.2%).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are in line with previous studies which demonstrated that neither ADT nor chemotherapy can achieve adequate palliation for the management of locally progressing and symptomatic prostate cancer [23][24][25]. Leibovici et al [24] treated 38 patients with locally advanced primary or recurrent disease by cystoprostatectomy, which led to significant and permanent reduction of symptoms in 30 patients (88.2%).…”
Section: Discussionsupporting
confidence: 90%
“…Four studies stated median survival post-PCN that ranged between 4–21 months [9, 11, 14, 15]. The other three studies stated their mean survival time as 31, 4.4 and 15 months respectively [5, 12, 13].…”
Section: Resultsmentioning
confidence: 99%
“…Malik et al briefly mention a complication rate of 4–26%, which was the same in bilateral and unilateral insertion, but did not document what these complications were [13]. Of the other 3 studies, two did not document any complications [9, 12] and one reported no complications post-PCN [14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations